THE EFFECT OF PER CAPITA EXPENDITURE ON POVERTY WITH THE HUMAN DEVELOPMENT INDEX AS A MODERATING VARIABLE - Budiasih, Yanti; Supiati, Supiati; Lestari, Eko Budi; Hendratri, Bhaswarendra Guntur; Setiawan, Heri (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract This research is quantitative research with an explanatory approach, namely making a number of previous studies related to Per Capita Expenditure, Human Development Index, and Poverty like a reference mirror which is used as the main source in finding elements of novelty and research gaps in the research being carried out. The data used in the research is secondary data that researchers obtained from the annual reports of the Central Statistics Agency from 2017 to 2024 respectively. Researchers analyzed these data using the smart PLS 4.0 analysis tool in several sequential stages, namely validity testing, reliability testing and path coefficients. The result in this researc show the Per Capita Income variable can have a positive relationship and a significant influence on the Poverty variable because the P-Values value is below the 0.05 significance level, namely 0.008. This is because the greater the per capita expenditure, the more people's consumption costs will increase and in the end it will bring people closer to the brink of poverty and even into it. Apart from that, in the second hypothesis which can be seen from the second row of the third table, the Path Coefficient can be concluded if the Human Development Index variable cannot strengthen the influence of the Per Capita Expenditure variable on Poverty because the higher the Human Development Index makes people smarter and less willing to spend their money on things. which is not urgent. These results were obtained from the P-Values which were above the significance level of 0.232. Thus, the first hypothesis in this research can be accepted, while the second hypothesis cannot be accepted. Keywords: Per Capita Expenditure, Poverty, Human Development Index